IMPLEMENTASI GUIDED INQUIRY LEARNING BERBANTUAN SIMULASI INTERAKTIF PhET UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS - Dian Nurfahzuni; Mohammad Budiyanto (PENSA: E-JURNAL PENDIDIKAN SAINS, 2023)
This study aimed to describe the improvement of students' science process skills by applying a guided inquiry learning model assisted by PhET interactive simulations in one of public Junior High School in Sidoarjo. This study used pre-experimental with a one-group pretest-posttest design. This study involved 17 students of class VII D in the Academic Year 2021/2022. Data collection methods through a observation, questionnaire, and test. The instrument of this study used observation sheets of learning implementation, science process skills tests (pretest and posttest), and student response questionnaires. The results of this study showed that the learning implementation had been carried out very well at each meeting. The learning outcomes of students’ science process skills increased significantly, based on the analysis of the average N-gain score in the medium criteria. Students gave positive responses to the learning that has been done with very good criteria. Based on the description above, it can be concluded that the learning used a guided inquiry model assisted by PhET interactive simulations was able to improve students’ science process skills.